The Pragmatics of “Really Mattering” on Policy Issues: William Ouchi as Exemplar - Weick, Karl E. (Academy of Management Journal, 2005)
The article discusses the contribution management scholar William Ouchi has made towards making management more relevant to policy issues. Ouchi has spent 35 years studying large business organizations, with a particular emphasis on how controls affect autonomy and outcomes within an organization. While studying a large public school system he determined that a key source of dysfunction was individual schools' lack of autonomy. When school principals are held accountable while having more scope for decision-making, Ouchi showed, the result was a more responsive system.